Há vida lá fora: o cotidiano das pessoas que moram nos serviços residenciais terapêuticos - Vieira, Fernanda Rodrigues (Universidade Federal de São Carlos, 2021)
The Residential Therapeutic Service (SRT) is a strategic device created for the restructuring of mental health care that enables people with severe psychological distress, institutionalized or not, to live in the urban space. Recognizing that it is the guarantee of the right to housing, to live and to live in the city, it is characterized as the first step in the difficult and complex process of reintegrating these people into society. Studies show that, in the scope of national and international research on the deinstitutionalization of people with psychological distress, there is little data on their reinsertion, especially those related to social and psychological aspects. The literature also explains the scarcity of research developed with the residents of the SRTs and that little is known about what they think about their daily lives. The present study aimed to understand the perception of residents of therapeutic residential services about their daily lives. It is a qualitative, exploratory and documentary research, with the participation of 8 residents of SRTs from a municipality in the interior of the state of São Paulo. Paulo. The concept of Daily Life underpins this research, from the perspectives of Occupational Therapy, Agnes Heller's Daily Life Theory and Psychosocial Rehabilitation, as they base the valuation of people in all their complexity and lead to the understanding of individual and collective factors that make part of the deinstitutionalization process. Data collection was carried out by consulting documents, reports and other information contained in the records of each participant and semi-structured interviews. The data from the documentary research were analyzed descriptively. Thematic analysis was used to treat the data produced through the interviews. The results were analyzed from the perspective of Occupational Therapy, above all, based on concepts that make up the field, such as participation, autonomy and the meanings of human activity, which revealed the importance and meanings given by participants to the SRT and the activities of care with the house held there, in addition to the use and appropriation of this space that highlights the subjectivity of each participant, the relationship between residents and how they act in conflict situations within the house. Participation in activities outside the SRT appears in reports with different purposes, levels and degrees of engagement. The knowledge, knowledge and experiences reported in each life story show the participants' perception related to the objective and concrete point of view. They reveal knowledge related to doing practical, mainly related to work, since the greatest possibilities of lived experiences were related to this. The importance and meanings of doing, interests and the use of money were addressed, as well as new learnings, autonomy, plans and desires. We hope that this study can contribute to the construction of knowledge in the area of psychosocial care, more specifically, to aspects related to the housing of people with psychological distress, as well as to their daily lives and the processes of social inclusion.
There is life out there: the daily lives of people who live in residential therapeutic services
Keywords: Saúde mental; Serviço Residencial Terapêutico; Cotidiano; Terapia Ocupacional; Mental health; Residential Therapeutic Service; Daily life; Occupational Therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::MEDICINA::PSIQUIATRIA